An Interdisciplinary Approach to the Human Mind: Subjectivity, Science and Experiences in Change - Joranger, Line (Cultural Dynamics of Social Representation, 2018)
One of the main aims of modern mental health care is to understand a person's explicit and implicit ways of thinking and acting. So, it may seem like the ultimate paradox that mental health care services are currently overflowing with brain concepts belonging to the external, visible brain-world and that neuroscientists are poised to become new experts on human conduct. An Interdisciplinary Approach to the Human Mind shows that to create care that is truly innovative, mental health care workers must not only ask questions about how their conceptions of human beings and psychological phenomena came into being, but should also see themselves as co-creators of the mystery they seek to solve. Looking at the human being as a being with a biological body and unique subjective experiences, living in a reciprocal relationship with its sociocultural and historical environment, the book will provide examples and theories that show the necessity of an innovating, interdisciplinary mental health care service that manages to adapt its theory and methods to environmental, biological, and subjective changes. To this end, the book will provide an innovating psychology that offers a broad kaleidoscope of perspectives about the relations between the history of psychology, as a scientific discipline oriented to interpret and explain subject and subjectivity phenomenon, and the social construction of subjectified experience. This unique and timely book should be of great interest to critical and cultural psychologists and theorists; clinical psychologists, therapists, and psychiatrists; sociologists of culture and science; anthropologists; philosophers; historians; and scholars working with social and health theories. It should also be essential reading for lawyers, advocates, and defenders of human rights. The Open Access version of this book, available at https://www.taylorfrancis.com/books/9781315309682 has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 licence.